PEMILIHAN LOKASI TPS 3R DI KECAMATAN LEKOK, KABUPATEN PASURUAN DENGAN SISTEM INFORMASI GEOGRAFIS (SIG) - rezana_, margaretha (Institut Teknologi Nasional Malang, 2025)
Waste management in Lekok Sub-district is influenced by two main factors, namely the high volume of waste generated and the lack of waste management facilities and infrastructure, such as Waste Collection Sites (TPS) or TPS 3R. This study aims to analyze waste generation and determine the appropriate location for the construction of TPS 3R in Lekok District, Pasuruan Regency, East Java. The criteria for determining the location of TPS 3R refers to the Regulation of the Minister of Public Works Number 3 of 2013 concerning the Implementation of Waste Infrastructure and Facilities in Handling Household Waste and Similar Waste. Waste generation measurements were conducted based on SNI 19-3964-1994, while location feasibility analysis used Geographic Information System (GIS) by utilizing buffer, scoring, and overlay features in ArcGis 10.8 software. The results of the spatial analysis showed five locations that are suitable for the construction of TPS 3R, namely Pasinan Village (locations 1 and 5), Rowogempol Village (location 2), Jatirejo Village (location 3), and Branang Village (location 4). These five locations have met the criteria set out in the Minister of Public Works Regulation No. 03/2013. With the existence of TPS 3R in these locations, it is expected that waste management can be optimized and able to reduce the waste load that goes to the landfill